Nanoparticles and microfluidic devices in cancer research - Maia, F. Raquel (2020)
Cancer is considered the disease of the century, which can be easily understood considering its increasing incidence worldwide. Over the last years, nanotechnology has been presenting promising theranostic approaches to tackle cancer, as the development of nanoparticle-based therapies. But, regardless of the promising outcomes withinÂ in vitroÂ settings, its translation into the clinics has been delayed. One of the main reasons is the lack of an appropriateÂ in vitroÂ model, capable to mimic the true environment of the human body, to test the designed nanoparticles. In fact, most ofÂ in vitroÂ models used for the validation of nanoparticle-based therapies do not address adequately the complex barriers that naturally occur in a tumor scenario, as such as blood vessels, the interstitial fluid pressure or the interactions with surrounding cells that can hamper the proper delivery of the nanoparticles into the desired site. In this reasoning, to get a step closer to theÂ in vivoÂ reality, it has been proposed of the use of microfluidic devices. In fact, microfluidic devices can be designed on-demand to exhibit complex structures that mimic tissue/organ-level physiological architectures. Even so, despite microfluidic-basedÂ in vitroÂ models do not compare with the reality and complexity of the human body, the most complex systems created up to now have been showing similar results toÂ in vivoÂ animal models. Microfluidic devices have been proven to be a valuable tool to accomplish more realistic tumourâ s environment. The recent advances in this field, and in particular, the ones enabling the rapid test of new therapies, and show great promise to be translated to the clinics will be overviewed herein.